THE STRATEGIC DEVELOPMENT OF THE RENEWABLE ENERGY SECTOR IN MOLDOVA: MODELS FOR INVESTMENT MANAGEMENT - Nasalciuc, Irina (Economy and Sociology, 2023)
The periodic paradigm shifts operating on the energy markets require higher innovative approaches to facilitate the management of energy portfolios and the design of mechanisms for an accelerated renewable energy integration. Thus, international organizations, policy makers and managerial boards are continuously seeking for policy amendments and adjustments that would enhance the investments in the renewable energy sector and stimulate the transition towards the smart energy grids’ models. The current study aims to review and apply some of the existing models for the management of renewable energy investments, using as a case study Moldova’s economy structure and its statistical data. The study is based on systemic research methods, forecasting models and estimates to identify most productive management tactics, able to ensure the proper integration of smart energies into the energy network. The author presents a model for forecasting the demand of the renewable energy market in Moldova till 2025 and 2030 year with an emphasis on the electricity segment. It also points out opinions and estimates that reflect a different perspective on the effects of investments’ management at the electricity segment level and proposes solutions that may help decision-makers in the development and integration of the country's renewable energy policy. The study offers the necessary evidence and grounded solutions for attracting and promoting investments in renewable energy projects, whereas the obtained methodology and results have a general relevance for other countries in the region with emerging economies.